ʿUlūm al-Qurʾān and the Diffusion of a New Methodology: A Rare Female Contribution to Qur'anic Sciences. Issue 2 (June 2022) - Sayeed, Asma
Abstract : This article examines the contributions of Farida Zomorrod, a female Qur'anic Sciences professor who has devoted herself to developing al-manhaj al-muṣṭalaḥī, a recent methodological trajectory of Qur'anic sciences in contemporary Morocco. As a current of reformist thought, this approach calls for renewed engagement with the Qur'an, especially through the study of technical concepts that can unlock Qur'anic interpretations and meanings relevant to contemporary challenges. Although the field of 'women and the Qur'an' has grown in recent decades, it has focused primarily on feminist hermeneutics. Less attention has been paid to scholars such as Zomorrod, who has not aligned herself with Islamic feminism: a lacuna which this article aims to address in some measure.